2021
DOI: 10.1093/molehr/gaab027
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional changes through menstrual cycle reveal a global transcriptional derepression underlying the molecular mechanism involved in the window of implantation

Abstract: The human endometrium is a dynamic tissue that only is receptive to host the embryo during a brief time in the middle secretory phase, called the window of implantation (WOI). Despite its importance, regulation of the menstrual cycle remains incompletely understood. The aim of this study was to characterize the gene cooperation and regulation of menstrual cycle progression, in order to dissect the molecular complexity underlying acquisition of endometrial receptivity for a successful pregnancy; and to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…GO analysis demonstrated that DEGs in RIF were primarily enriched in lipid metabolism and immune processes. In KEGG analysis, the NF-κB, TNF, and adipocytokine signaling pathways were linked together, which is consistet with similar RIF studies showing dysregulated NF-κB and TNF pathways [ 24 , 38 , 39 , 40 ]. GSEA results demonstrated that RIF was significantly enriched in downregulated graft-versus-host disease, allograft rejection, complement and coagulation cascades, antigen processing and presentation, upregulated fatty acid biosynthesis, ovarian steroidogenesis, and steroid hormone biosynthesis.…”
Section: Discussionmentioning
confidence: 61%
“…GO analysis demonstrated that DEGs in RIF were primarily enriched in lipid metabolism and immune processes. In KEGG analysis, the NF-κB, TNF, and adipocytokine signaling pathways were linked together, which is consistet with similar RIF studies showing dysregulated NF-κB and TNF pathways [ 24 , 38 , 39 , 40 ]. GSEA results demonstrated that RIF was significantly enriched in downregulated graft-versus-host disease, allograft rejection, complement and coagulation cascades, antigen processing and presentation, upregulated fatty acid biosynthesis, ovarian steroidogenesis, and steroid hormone biosynthesis.…”
Section: Discussionmentioning
confidence: 61%
“…In this complex physiological process, numerous of molecular mediators participate in the initial maternal-fetal interaction under the coordination of ovarian steroid hormones [34]. Although it is known that ovaries produce many steroids throughout the menstrual cycle, only E2 and P have been proven to be essential for inducing endometrial receptivity [5,35]. Studies have shown that the disorder of the sex hormone will affect the endometrial receptivity [36,37], and low serum progesterone on day of transfer adversely impacts ongoing pregnancy rates in hormonally prepared single blastocyst frozen embryo transfer cycles [38].…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial receptivity refers to the period of endometrial maturation during which the trophectoderm of the blastocyst can attach to the endometrial epithelial cells and subsequently invade the endometrial stroma and vasculature [4]. As in humans, the endometrium undergoes a series of dynamic and complex changes during the menstrual cycle, and blastocysts are allowed to implant in a brief period, this period is called window of implantation (WOI), which is usually around days 19-24 of the menstrual cycle [5]. However, the WOI of each woman has an individual variation, and some women will have displace-WOI, this may lead to embryo-endometrium asynchrony, which usually leads to implantation failure or even recurrent implantation failure (RIF) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Finding robust biomarkers for RIF is important for RIF prediction, diagnosis, and treatment. Researchers have characterized genetic cooperation and regulation through the menstrual cycle progression and characterized the genetic profiles for the acquisition of endometrial receptivity for a successful pregnancy (13). Recently, a panel of endometrial biomarkers acquired by endometrial receptivity test (ERT) was developed to accurately predict the window of implantation (WOI) and significantly improve the pregnancy outcomes of patients with RIF.…”
Section: Introductionmentioning
confidence: 99%